A Bibliometric Analysis of Research Trends in Guidance Office Support Systems - Kizea Bien S. Igaya; John Vincent F. Tiu; Mark Ivan J. Villaster; Jennifer P. Solis (Future Science / FSH-PH Publications, 2026)
This study presents a bibliometric analysis of the research on guidance office support systems to better understand the emerging trends in this field. At this point, a more developed technology, guidance office support systems show importance in addressing the needs of students, even in terms of academic, personal, and well-being of students, making it a need to examine how research in this field is being discussed and evolves over time. With the use of the Scopus database, 293 documents were collected, but it decreased to a total of 288 documents after they were cleaned by removing duplicates and Using TRIM() Function to unwanted spaces in Excel. The cleaned dataset with 288 documents was analyzed using the Bibliometrix package in R Studio. The Biblioshiny interface was used to generate the bibliometric indicators and visualizations, which include keyword networks, institutional productivity charts, and citation analysis, which helps to identify the major research themes and publications within the dataset. For the analysis of the dataset, Most Relevant Affiliations, Most Global Cited Documents, Word Cloud, and Density Co-occurrence Network are used to understand how the field has evolved over time. Results show that research interest in digital support for guidance offices is steadily increasing, with leading institutions consistently producing studies related to guidance office support systems.